Facelift Approach for Parotidectomy: An Evolving Aesthetic Technique. Issue 4 (4th February 2013) - Grover, Nancy; D'Souza, Alwyn
Abstract : Objective: To systematically review the literature on the modified facelift incision for parotidectomy and to identify the scope and safety of this approach, along with cosmetic outcomes. Where available, a direct comparison was made with Blair's incision (BI). Data Sources: Medline, PubMed, Cochrane, and CINHAL databases for English‐language studies published between 1960 and 2011 on the facelift approach for parotidectomy. Review Methods: Exclusion criteria were studies reporting on concurrent facelift, studies that used synthetic material for reconstruction of the surgical bed, descriptive studies, and studies with duplicate patient data. Outcome measures were candidacy for surgery, variations in incision, cosmetic outcomes, surgical time, complication rates, and limitations. Results: Of the initial 139 studies, 11 studies encompassing 628 patients were included. Male‐to‐female ratio was 0.49:1, and average age was 47.1 years. In total, 582 surgeries were performed for benign lesions. Only 10 studies specified the extent of surgery: 8 authors used it for performing superficial/partial parotidectomy, and 2 described 17 cases of total parotidectomy. Tumors up to 8 cm have been excised, with a median value of 4 cm. Operative time, formally analyzed in 3 studies, was not significantly different when compared with BI. Complication rates were not increased with this approach. Aesthetic outcomes pertaining to postoperative scar were good, as reported by the patients. Conclusion: The facelift approach is a cosmetically superior approach to parotid tumors as proven by objective data. Most publications in the literature pertaining to the modified facelift incision for parotidectomy have been in the past decade, lending credence to its rising popularity.